Real-time video content for virtual production & live entertainment a learning roadmap for an evolving practice - Frank, Laura (Routledge, 2023)
"Real-Time Video Content for Virtual Production & Live Entertainment looks at the evolution of current software and hardware, how these tools are used, and how to plan for productions dependent on real-time content. From rock concerts to theatre, live television broadcast to film production, art installations to immersive experiences, the book outlines the various applications of real-time video content - the intersection of gaming and performance that is revolutionizing how films are made and how video content is created for screens. Rather than render out a fixed video file, new tools allow for interactive video content that responds to audience activity, camera position, and performer action in real time. Combining software renderers with environmental information, video content is generated nearly instantaneously to simulate depth, creating a new world of virtual production. This book provides an overview of the current software and hardware used to create real-time content while also reviewing the various external technologies the real-time content is dependent upon. Case studies from industry experts appear in each chapter to reinforce the tools described, establish industry practice, and provide insight on a complex and rapidly growing discipline. Real-Time Video Content for Virtual Production & Live Entertainment prepares students and practitioners for a future working with real-time technologies and informs current entertainment technology professionals how to rethink about their old roles using these new tools. The book includes access to a companion website featuring web-based and video resources that expand on topics covered in the text. Each chapter has a unique page that points to example material, video presentations, and professional studies on chapter topics. You can visit the companion website at rtv-book.com"--